Os periódicos brasileiros e a comunicação da pesquisa nacional - Packer, Abel L. (Revista USP, 2011)
Brazilian journals occupy an important space and play an important role in imparting scientific research. Published mainly in open-access format, they enjoy high visibility and accessibility. Besides publishing over one third of the articles by authors affiliated to Brazilian institutions which are indexed in international databases, Brazilian journals contribute to balancing the multilingual communication of scientific production, mainly in leading knowledge areas in the country. Its future development emerges as a strategic agenda of policies geared towards supporting Brazilian research. Such noteworthy presence is contrasted by a poor average performance, much lower than that of journals in developed countries, measured by the number of citations each article receives. Such performance affects the impact of Brazilian research as a whole. Although that performance is due partially to the classical factors influencing the practice of citations, such as the language in which the article is published, theme area and international cooperation, improving Brazilian journals demands public policies to help overcome their limitations.